Рівень комплексів антиген-антитіло у хворих на рак щитоподібної залози у ранній термін після радіойодотерапії залежно від віку - Степура, Н. М.; Замотаєва, Г. А. (Clinical Endocrinology and Endocrine Surgery, 2013)
The age is one of the important factors that modifies the effect of radiation exposure on the organism. In this connection, a study of the immune system of thyroid cancer patients of different age after radioiodine therapy – and, in particular, determination of the levels of circulating immune complexes – are of a scientific interest. The authors present data on the content of antigen-antibody complexes in 86 patients with thyroid carcinoma early after radioiodine therapy. Patients were divided into three groups: children and adolescents aged 13 to 18 years (average: 16,0±0,3); young adults aged 19 to 40 years (average: 28,4±1,02); and the oldest age group from 41 to 70 years (average: 53,8±1,4). Age-matched donors served as controls. Levels of circulating immune complexes were measured before and 6 days after receiving radioiodine. It has been established that on the eve of radioiodine therapy, in all age groups of patients the number of immune complexes was significantly higher compared to control values and almost did not differ between the groups under study. It has been shown that in short terms after iodine-131 administration, significantly increased levels of circulating immune complexes were noted only in patients aged 21 to 40 years. It would be appropriate to study the dynamics of immune complexes formation in patients of different age after radioiodine administration in order to determine possible age-related differences.